Peranan Penyuluh Pertanian dalam Penerapan Pupuk Organik pada Kelompok Tani Harapan Makmur di Tegalsari, Jember - Fatika Zahfia Riasti; Lenny Luthfiyah; Sofia; Rokhani (AGRIFITIA : Journal of Agribusiness Plantation, 2026)
The decline in rice productivity in Tegalsari Village, Ambulu District, Jember Regency, demonstrates the need for a more sustainable agricultural system. Farmers' dependence on chemical fertilizers and the limited availability of subsidized fertilizers encourage the development of organic fertilizers as an alternative to improve soil quality and maintain sustainable production. However, the adoption rate of organic fertilizers among farmers remains relatively low despite the significant potential of livestock waste. This situation requires the active role of agricultural extension workers. This study aims to analyze the role of agricultural extension workers in the application of organic fertilizers in the Harapan Makmur Farmers Group. The study used a qualitative approach with a case study design. The research informants consisted of 16 individuals, comprising one agricultural extension worker and fifteen farmers, who were selected purposively. Data collection was conducted through moderate observation, semi-structured in-depth interviews, and documentation. Data were analyzed using Miles and Huberman's interactive analysis model, which involves data reduction, data presentation, and conclusion drawing. The validity of the research data was tested through source and technique triangulation. The research results show that agricultural extension workers play a role in education, innovation dissemination, facilitation, consultation, supervision, monitoring, and evaluation in encouraging the adoption of organic fertilizers. This role has been able to improve farmers' knowledge and skills, although adoption rates vary and are uneven. However, the role of consultation and evaluation has not been optimal. Limited consultation intensity and the lack of measurable evaluation data hinder the role of extension workers in optimizing the sustainable application of organic fertilizers.   ABSTRAKPenurunan produktivitas padi di Desa Tegalsari, Kecamatan Ambulu, Kabupaten Jember menunjukkan perlunya penerapan sistem pertanian yang lebih berkelanjutan. Ketergantungan petani terhadap pupuk kimia serta keterbatasan pupuk bersubsidi mendorong pengembangan penggunaan pupuk organik sebagai alternatif untuk memperbaiki kualitas tanah dan menjaga keberlanjutan produksi. Namun, tingkat adopsi pupuk organik di kalangan petani masih relatif rendah meskipun terdapat potensi besar limbah ternak. Kondisi ini memerlukan peran aktif penyuluh pertanian. Penelitian ini bertujuan menganalisis peranan penyuluh pertanian dalam penerapan pupuk organik pada Kelompok Tani Harapan Makmur. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Informan penelitian berjumlah 16 orang yang terdiri atas satu penyuluh pertanian dan lima belas petani yang dipilih secara purposive. Pengumpulan data dilakukan melalui observasi moderat, wawancara mendalam semi-terstruktur, dan dokumentasi. Data dianalisis menggunakan model analisis interaktif Miles dan Huberman melalui reduksi data, penyajian data, dan penarikan kesimpulan.  Uji keabsahan data penelitian ini dilakukan melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa penyuluh pertanian menjalankan peran edukasi, diseminasi inovasi, fasilitasi, konsultasi, supervisi, pemantauan, dan evaluasi dalam mendorong penerapan pupuk organik. Peran tersebut mampu meningkatkan pengetahuan dan keterampilan petani, meskipun tingkat adopsi masih bervariasi dan belum merata. Namun, peran konsultasi dan evaluasi belum optimal. Keterbatasan intensitas konsultasi serta belum tersedianya data evaluasi yang terukur menjadi kendala pada peran penyuluh dalam optimalisasi penerapan pupuk organik secara berkelanjutan.